Innovation Performance Measurement and Investment Effectiveness in Industrial Enterprises: A Multidimensional and Institutional Approach - Gafurova Umida Fatikhovna (THE PLACE AND ROLE OF TURKEY AND THE NEAR REGION IN THE PROCESSES OF SCIENTIFIC, SOCIAL, AND CULTURAL DEVELOPMENT, 2026)
In the context of intensifying global competition, ensuring sustainable economic growth, accelerating scientific and technological progress, and enhancing the effectiveness of innovation activity has become one of the central priorities of state economic policy. In Uzbekistan, the ongoing structural reforms—particularly those aimed at industrial modernization, digital transformation, and the expansion of importsubstituting production have significantly increased the need for a scientifically grounded assessment of enterprises’ innovation performance. Under these conditions, improving the methodological foundations for evaluating innovation effectiveness, revising existing assessment frameworks, and adapting them to the evolving economic environment emerges as a critically important research and policy task.